Penggunaan Sosiometri Dalam Layanan Bimbingan Konseling - Ade Chita Putri Harahap; Ahsanul Hakim Hasibuhan; Annissa Zuhra; Deni Rizky Wahyudi ; Ikrimah Amalah Batubara; Mitha Amelia Dalimunthe; Nurmiah Hasibuhan; Wulan Sari Dalimunthe (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Sociometry is a technique for gathering information about the structure and patterns of relationships between people in groups. This approach is based on the idea that groups have structures made up of complex interpersonal connections. Everyone's position and relationships within the group structure can be measured and evaluated qualitatively. The results of sociometry processing will provide an overview of the distribution of each person's score, the relationship structure, intensity, and position in the student group. Keywords: Sociometry, counseling guidance